Principles and applications of assessment in counseling - Whiston, Susan C. (Australia ; Belmont, CA : Brooks/Cole, Cengage Learning, 2009)
This text is an introduction to appraisal and assessment targeted at counselling students. It presents mathematical and statistical concepts in a useful manner, stressing the importance of counsellors being good consumers of assessment tools to avoid misusing tools in manners harmful to clients.
Includes bibliographical references (p. [450]-473) and index.
Keywords: Counseling; Psychodiagnostics